2000
DOI: 10.1016/s1074-7613(00)00031-5
|View full text |Cite
|
Sign up to set email alerts
|

The CD28 and CTLA-4 Receptors Associate with the Serine/Threonine Phosphatase PP2A

Abstract: CD28 and CTLA-4 are related members of a family of T lymphocyte cell surface receptors that function to regulate T cell activation. We have found that the cytoplasmic domains of both CTLA-4 and CD28 can associate with members of the PP2A family of serine/threonine phosphatases. The association of PP2A with CD28 was negatively regulated by tyrosine phosphorylation of the CD28 cytoplasmic domain. Inhibition of PP2A activity in Jurkat leukemia T cells by treatment with okadaic acid or by expression of a dominant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
219
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(232 citation statements)
references
References 47 publications
6
219
1
1
Order By: Relevance
“…Activated or memory-type T cells including T cell clones may be susceptible to an alternative inhibitory mechanism through TR-CTLA-4 that does not require the cytoplasmic domain of CTLA-4. Since it is clear that the present study more closely reflects physiological function than the previous study, the obvious requirement of the cytoplasmic domain of CTLA-4 for its inhibitory function may suggest the importance of the assembly of the CTLA-4 tail with inhibitory molecules including SHP-2 [18,20] or regulatory molecules such as PP2A [22,23]. Further studies are needed to clarify the in vivo inhibitory mechanism through CTLA-4 in different stages of T cell development.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Activated or memory-type T cells including T cell clones may be susceptible to an alternative inhibitory mechanism through TR-CTLA-4 that does not require the cytoplasmic domain of CTLA-4. Since it is clear that the present study more closely reflects physiological function than the previous study, the obvious requirement of the cytoplasmic domain of CTLA-4 for its inhibitory function may suggest the importance of the assembly of the CTLA-4 tail with inhibitory molecules including SHP-2 [18,20] or regulatory molecules such as PP2A [22,23]. Further studies are needed to clarify the in vivo inhibitory mechanism through CTLA-4 in different stages of T cell development.…”
Section: Discussionmentioning
confidence: 63%
“…Although it has been suggested that several molecules, such as Src homology 2-containing protein tyrosine phosphatase-2 (SHP-2) and phosphatidyl inositol 3-kinase (PI3K), may mediate the negative signal through binding to the phosphorylated tyrosine motif (YVKM) present in the cytoplasmic region of CTLA-4 [18][19][20], the precise inhibitory mechanism remains controversial [21][22][23]. We and others have previously shown that the PI3K/ SHP-2 binding sites are not essential for CTLA-4-mediated inhibitory signals in T cell clones/cell lines [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been also shown that PD-1 blocks the CD28-mediated activation of phosphatidylinositol-3-kinase (PI3K) and the serinethreonine kinase Akt by recruiting SHP2, whereas CTLA-4 directly inhibits Akt, but not PI3K activation, possibly by the association with protein phosphatase 2A (PP2A) (Parry et al, 2005). However, CTLA-4 is also known to be associated by SHP2 and/or SHP1, and PP2A binds both CD28 and CTLA-4 (Chuang et al, 2000). Furthermore, PI3K is activated downstream of not only CD28 but also TCR and CTLA-4 (Rudd and Schneider, 2003).…”
Section: Pd-1 Accumulation At Tcr Microclustersmentioning
confidence: 99%
“…Proposed mechanisms include ligand competition with the costimulatory molecule CD2 , activation of inhibitory signaling pathways 93 and effects on membrane lipid rafts. 94 Recently, it has been shown that, in the presence of antigen, T cells expressing CTLA-4 continue their random migration at unchanged velocities, whereas CTLA-4-null T cells slow down and form long-lasting conjugates with APCs.…”
Section: Future Research On the Ismentioning
confidence: 99%